ANALYSIS OF THE EFFECT OF STOCK SPLIT AND CAPITAL STRUCTURE ON STOCK LIQUIDITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2018-2020 PERIOD - MITA, SUSMITA SARI (Indragiri Research Center (ingreat), 2023)
This study aims to find out whetherstock split and the capital structure affects the liquidity of shares in manufacturing companies listed on the IDX for the 2018-2020 period. The research population is manufacturing companies listed on the IDX in 2018-2020. Sampling using techniquePurposive Sampling. The sample consisted of 21 companies from 26 manufacturing companies listed on the IDX for 2018-2020, so that the research data analyzed totaled 63 samples. The data analysis technique used was Multiple Linear Analysis. Based on the results of research using the coefficient of determination test (R2) yield 12.4%Stock Split and Capital Structure jointly affect Stock Liquidity, while the remaining 87.6% is influenced by other variables not examined in this research variable. From the results of the multiple linear regression test, the regression equation is Y = 20.763 + 0.356 X1 + 0.397 X2 + ε. Based on the results of the (Partial) T-test research, it shows that Variable stock split have t-count as big-0,311 smaller than t-table namely 1.6706 until tcount< ttable HO accepted and Ha rejected and the sig value of 0.437 is greater than 0.05, so it can be concluded that partially Stock Split has no effect and is not significant to the Liquidity of Shares. The Capital Structure Variable has t-count as big2,889 while t-table namely 1.6706 until tcount>ttable, HO rejected and Ha accepted and the sig value of 0.005 is less than 0.05 so it can be concluded that partially Capital Structure has a significant and significant effect on Stock Liquidity. From F test (Simultaneous) F value is obtainedcount of 4.240 while Ftable of 3.15 so it can be concluded that Stock Split and Capital Structure simultaneously have a significant influence on Stock Liquidity.